A novel microdeletion affecting the CETP gene raises HDL‐associated cholesterol levels. Issue 4 (23rd July 2015) - Hitchcock, E.; Patankar, J.V.; Tyson, C.; Hrynchak, M.; Hayden, M.R.; Gibson, W.T.
Abstract : We describe a novel, inherited 16q13 microdeletion that removes cholesteryl ester transfer protein ( CETP ) and several nearby genes. The proband was originally referred for severe childhood‐onset obesity and moderate developmental delay, but his fasting lipid profile revealed relatively high levels of high density lipoprotein cholesterol (HDL‐C) and relatively low levels of low density lipoprotein cholesterol (LDL‐C) for age, despite his obesity. Testing of first‐degree relatives identified two other microdeletion carriers. Functional assays in affected individuals showed decreased CETP mRNA expression and enzymatic activity. This microdeletion may or may not be pathogenic for obesity and developmental delay, but based on the lipid profile, the functional studies, and the phenotype of other patients with loss‐of‐function mutations of CETP, we believe this microdeletion to be antipathogenic for cardiovascular disease.